Proposed Competitive Strategy for JD.ID in Indonesia's E-commerce Industry - Dian Agustine, Aubrey; Purwoko Kusumo Bintoro, Bambang (The Indonesian Journal of Business Administration, 2017)
Abstract. The existence of e-commerce has change the way people purchase products or services. Customers are slowly get used to purchase products through E-commerce as a substitute of traditional brick and mortar stores. Indonesia as the fourth largest population in world has big potential for e-commerce business development. Along with this opportunity, JD.ID, started to operate in Indonesia on 2016. As a new comer in the industry, JD.ID is trying to gain market’s recognition and compete the existing competitors. The objective of this study is to analyze the current condition of the industry, the current business strategy of JD.ID and to formulate business solution in order to enhance JD.ID’s competitiveness in  Indonesian E-commerce industry. There are three problems addressed in this study. First is the current condition in E-commerce industry. Second question is the current JD.ID business strategy, and the last question is competitive strategy for JD.ID in e-commerce industry. According to the external analysis, Indonesian ecommerce industry is very competitive industry. Furthermore, the internal analysis of JD.ID shows that it is favorable to expand. Regarding to the current company’s situation, some alternative of business solution are generated using the combination of TOWS and Five Diamond Analysis. In order to increase the company's competitiveness, the author proposed a set of business strategy that focusing on 3 department in the firm, marketing, merchandising and  logistic and operation.Keywords: e-commerce, JD.ID, competitive strategy, online shopping, online retailer.